Connective Action Narratives of Latin American Migrant Women with Transmedia Reading Experience - Pacheco Díaz, Angélica (2023)
If narratives generate community and stories encourage the ability for empathy by creating bonds between people (Han, 2023), then the creation of meaningful tales becomes a necessary path for the construction of the ordinary. In this sense, in this article, the construction of common imaginaries through tales of connective and transmedia action is investigated in the biographical space of Latin American migrant women, by using a qualitative methodology and a non-random sample of Latin American migrant women in Canada, the United States, and Europe, who participated in the publication Imaginarios de Mujeres Latinoamericanas (Imaginaries of Latin American women) (Pacheco, et., 2022). Among the results, collaborative practices of net weaving learned in their places of origin were identified, being this weave of the warp the force of life of the migrants who move from a biographical space towards otherness, integrating their life stories in the ordinary.